2017
DOI: 10.4238/gmr16029601
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Colletotrichum isolates from Capsicum chinense in Amazon

Abstract: Chili pepper (Capsicum chinense) is a great economic important culture on the State of Amazonas, and it represents, approximately, a production of 1.9 thousand tons per year. It is one of the hosts of Colletotrichum genus in the North region of Brazil. The aim of the study was to differentiate and to identify isolates of Colletotrichum collected from C. chinense in Amazon. Molecular characterization, using RFLP-PCR, ERIC-PCR and ISSR, was carried out initially for screening of morphologically similar isolates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Within the C. siamense clade, small subclades were observed that coincided with different geographical regions from where the isolates were collected. Colletotrichum siamense has been reported to infect chili in Asia, Australia, Brazil, and is a common pathogen of many other plant species (Weir et al 2012;James et al 2014;Liu et al 2016aLiu et al , 2016bde Oliveira et al 2017;De Silva et al 2017a;Diao et al 2017;Suwannarat et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Within the C. siamense clade, small subclades were observed that coincided with different geographical regions from where the isolates were collected. Colletotrichum siamense has been reported to infect chili in Asia, Australia, Brazil, and is a common pathogen of many other plant species (Weir et al 2012;James et al 2014;Liu et al 2016aLiu et al , 2016bde Oliveira et al 2017;De Silva et al 2017a;Diao et al 2017;Suwannarat et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that at least 12 species (Figure 1B) of Colletotrichum are pathogenic to Capsicum spp. in Brazil (TOZZE Jr. et al 2009;PEREI-RA et al 2011;CAIRES et al 2014;ALMEIDA 2015;LIMA et al 2015;ALMEIDA et al 2017;OLIVEIRA et al 2017;SILVA et al 2017c;GIACOMIN et al 2021) highlights the importance and complexity of this pathosystem.…”
Section: What Does One Need To Know Before Starting a Capsicum Breedi...mentioning
confidence: 99%